1996
DOI: 10.1097/00003246-199608000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Calf's lung surfactant extract in acute hypoxemic respiratory failure in children

Abstract: Administration of calf's lung surfactant appears to be safe and is associated with rapid improvement in oxygenation and moderation of ventilator support in children with acute hypoxemic respiratory failure. These results set the stage for a randomized, controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…A number of uncontrolled and controlled studies have documented clinical benefit from exogenous surfactant replacement therapy in term infants, children, and adults with acute respiratory failure (ALI/ARDS) [66][67][68][69]154,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200] ( Table 2). Of the 19 positive studies listed in Table 2, 9 were controlled trials [67][68][69]154,192,[197][198][199][200] and 10 were uncontrolled treatment trials, in which the risk of selection bias is inherent.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of uncontrolled and controlled studies have documented clinical benefit from exogenous surfactant replacement therapy in term infants, children, and adults with acute respiratory failure (ALI/ARDS) [66][67][68][69]154,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200] ( Table 2). Of the 19 positive studies listed in Table 2, 9 were controlled trials [67][68][69]154,192,[197][198][199][200] and 10 were uncontrolled treatment trials, in which the risk of selection bias is inherent.…”
Section: Human Studiesmentioning
confidence: 99%
“…That trial followed an initial uncontrolled treatment study by the same group, which found improved oxygenation in 24 children (ages 0.1-16 y) with ALI/ ARDS treated with instilled calfactant. 191 A controlled study by Moller et al 199 also reported that children with ARDS showed immediate oxygenation improvement and less need for rescue therapy following treatment with beractant, but the trial was underpowered to assess more definitive longer-term outcomes. A larger and more recent blinded controlled study in 2005 by Willson et al, 154 in patients up to age 21 years with ALI/ARDS, found that treatment with calfactant, relative to placebo, was associated with immediate oxygenation benefit and a significant survival advantage (Table 3).…”
Section: Human Studiesmentioning
confidence: 99%
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…Studies of surfactant therapy in children and adults with ALI/ARDS show positive results in a number of case reports or relatively small pilot trials [120,121,[124][125][126][127][128]. However, particularly in adults, controlled clinical trials have been less successful.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
See 1 more Smart Citation